2024
DOI: 10.1002/anie.202405426
|View full text |Cite
|
Sign up to set email alerts
|

A Naphthalenetetracarboxdiimide‐Containing Covalent Organic Polymer: Preparation, Single Crystal Structure and Battery Application

Qiang Dong,
Tuoya Naren,
Lei Zhang
et al.

Abstract: Inspired by dative boron‐nitrogen (B←N) bonds proven to be the promising dynamic linkage for the construction of crystalline covalent organic polymers/frameworks (COPs/COFs), we employed 1,4‐bis(benzodioxaborole) benzene (BACT) and N,N'‐Di(4‐pyridyl)‐1,4,5,8‐naphthalenetetracarboxdiimide (DPNTCDI) as the corresponding building blocks to construct a functional COP (named as CityU‐25), which had been employed as an anode in rechargeable lithium ion batteries. CityU‐25 displayed an excellent reversible lithium st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…The era of energy diversification reflects the wisdom progress of human civilization, but limited earth resources need to be rationally allocated to maximize their utilization efficiency. Faced with the rising demand for sharp energy density iteration, the exploitation of highly efficient energy storage devices becomes an urgent need. Lithium–sulfur batteries (LSBs) have been widely studied because of these advantages, such as high energy density (especially up to 2600 Wh kg –1 ), high theoretical specific capacity of active sulfur (1675 mAh g –1 ), and abundant resources. However, these issues perplex the research process of LSBs, including the unstable cathode frameworks caused by volume expansion/shrinkage for sulfur redox reaction (SRR) during charging/discharging cycles, the untimely transformation of lithium polysulfides (LiPSs), inferior conductivity of sulfur source (S 8 ) and low-order phase reaction products (Li 2 S 2 and Li 2 S), and the lithium dendrites on the anode, restricting its commercial exploration. In particular, the shuttle effect of dissolvable LiPSs (mainly Li 2 S 8 –Li 2 S 4 ) not only injures the mass transfer reaction of SRR within the cathode (a mass of intermediates travel to the anode side) but also causes the out-of-order deposition/stripping of active substances lithium (inactive dead-sulfur and dead-lithium are clustered in microzones). …”
Section: Introductionmentioning
confidence: 99%
“…The era of energy diversification reflects the wisdom progress of human civilization, but limited earth resources need to be rationally allocated to maximize their utilization efficiency. Faced with the rising demand for sharp energy density iteration, the exploitation of highly efficient energy storage devices becomes an urgent need. Lithium–sulfur batteries (LSBs) have been widely studied because of these advantages, such as high energy density (especially up to 2600 Wh kg –1 ), high theoretical specific capacity of active sulfur (1675 mAh g –1 ), and abundant resources. However, these issues perplex the research process of LSBs, including the unstable cathode frameworks caused by volume expansion/shrinkage for sulfur redox reaction (SRR) during charging/discharging cycles, the untimely transformation of lithium polysulfides (LiPSs), inferior conductivity of sulfur source (S 8 ) and low-order phase reaction products (Li 2 S 2 and Li 2 S), and the lithium dendrites on the anode, restricting its commercial exploration. In particular, the shuttle effect of dissolvable LiPSs (mainly Li 2 S 8 –Li 2 S 4 ) not only injures the mass transfer reaction of SRR within the cathode (a mass of intermediates travel to the anode side) but also causes the out-of-order deposition/stripping of active substances lithium (inactive dead-sulfur and dead-lithium are clustered in microzones). …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, organic polymer electrode materials have offered a promising strategy due to their nonintercalation redox mechanism. Their effective application in a range of rechargeable batteries has already sparked global interest. For instance, Liang et al reported that poly(anthraquinonyl sulfide) (PAQS) exhibits a persistently low voltage polarization at −25 °C . Qin et al reported an all-organic battery that realized 79% capacity release when the temperature dropped even to −80 °C .…”
Section: Introductionmentioning
confidence: 99%